Dead man's folly - Christie, Agatha, 1890-1976. (New York : HarperPaperbacks, 1984)
Hercule Poirot is summoned by his old acquaintance, writer-detective Ariadne Oliver, to attend a "Murder Hunt" at Nasse House in Devonshire.
Young Adult
Keywords: Poirot, Hercule (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Mystery fiction; Poirot, Hercule (Fictional character) -- Fiction; Private investigators -- Fiction; Detective and mystery stories